Impact of October Snow Cover in Central Siberia on the Following Spring Extreme Precipitation Frequency in Southern China - Zhang, Mengqi; Sun, Jianqi (Frontiers in Earth Science, 2021)
Spring extreme precipitation poses great challenges to agricultural production and economic development in southern China. From the perspective of prediction, the relationship between spring extreme precipitation frequency (SEPF) in southern China and preceding autumn Eurasian snow cover over Eurasia is investigated. The results indicate that the southern China SEPF is significantly correlated with October snow cover in central Siberia. Corresponding to reduced October snow cover, the vertical propagation of planetary waves is suppressed, which leads to a strengthened stratospheric polar vortex from October to following December. The signal of the anomalous stratospheric polar vortex propagates downward to the surface, contributing to a positive North Atlantic Oscillation (NAO)-like pattern in December. The southwesterlies in the northern Eurasia-eastern Arctic associated with the positive NAO induce sea ice loss in the Barents–Kara seas in January–February, which then tends to enhance the vertical propagation of planetary waves by constructively interfering with the climatological wavenumber-1 component. Therefore, the stratosphere polar vortex is significantly weakened in spring, which further contributes to a negative Arctic Oscillation (AO)-like pattern in the troposphere. The negative spring AO is related to an anomalous cyclone in East Asia, which induces upward motion and moisture convergence in southern China, consequently providing favorable dynamic and moisture conditions for extreme precipitation in the region. The snow cover signal in central Siberia in the preceding October provides a potential source for the prediction of spring extreme precipitation variability in southern China with two seasons in advance.